MicroRNAs involved in chemo- and radioresistance of high-grade gliomas - Besse, Andrej; Sana, Jiri; Fadrus, Pavel; Slaby, Ondrej (Tumour biology, 2013)
High-grade gliomas (HGGs) are malignant primary brain tumors of glial cell origin. Despite optimal course of treatment, including maximal surgical resection followed by adjuvant chemo- and/or radiotherapy, the prognosis still remains poor. The main reason is the commonly occurring chemo- and radioresistance of these tumors. In recent years, several signaling pathways, especially PI3K/AKT and ATM/CHK2/p53, have been linked to the resistance of gliomas. Moreover, additional studies have shown that these pathways are significantly regulated by microRNAs (miRNAs), short endogenous RNA molecules that modulate gene expression and control many biological processes including apoptosis, proliferation, cell cycle, invasivity, and angiogenesis. MiRNAs are not only highly deregulated in gliomas, their expression signatures have also been shown to predict prognosis and therapy response. Therefore, they present promising biomarkers and therapeutic targets that might overcome the resistance to treatment and improve prognosis of glioma patients. In this review, we summarize the current knowledge of the functional role of miRNAs in gliomas resistance to chemo- and radiotherapy.
Keywords: checkpoint kinasa 2; proteiny buněčného cyklu; mikro RNA; invazivní růst nádoru; Neoplasm Invasiveness; Humans; Checkpoint Kinase 2; Tumor Suppressor Proteins; nádorové supresorové proteiny; gliom; Glioma; chemorezistence; protoonkogenní proteiny c-akt; ATM protein; DNA-Binding Proteins; apoptóza; Radiation Tolerance; Tumor Suppressor Protein p53; Proto-Oncogene Proteins c-akt; nádorový supresorový protein p53; DNA vazebné proteiny; Ataxia Telangiectasia Mutated Proteins; Drug Resistance, Neoplasm; Cell Cycle Proteins; fosfatidylinositol-3-kinasy; protein-serin-threoninkinasy; Protein Serine-Threonine Kinases; tolerance záření; Brain Neoplasms; MicroRNAs; nádory mozku; lidé; Phosphatidylinositol 3-Kinases; Apoptosis